Aerodynamic design and numerical study for centrifugal turbine with different shapes of volutes. (25th February 2018) - Wang, Ying; Tan, Xin; Wang, Naian; Huang, Diangui
Highlights: Three-dimensional steady flow for the designed centrifugal turbine was studied. CFD simulation was conducted both in design and off-design conditions. Volutes with three types of cross section shapes were designed and applied. Aerodynamic performances are almost the same with three types of volutes. The pear shaped volute shows slightly higher total efficiency than other types. Abstract: Centrifugal turbine presents good aerodynamic and geometric compatibility. The straight blade can be directly used without significant effect on three dimensional flow field, and therefore the optimum values of the speed ratio and reaction degree can keep constant along the spanwise direction with higher turbine efficiency and simpler manufacturing. Furthermore, the closed impeller which is made by fixing the blade tip using cover band shows larger impeller strength and is suitable for high-speed rotation. In recent years, the centrifugal turbine with many potential advantages is gradually becoming a research hotspot in the field of turbine. In this paper, three kinds of volutes with different cross section shapes were designed for a single-stage centrifugal turbine unit. Based on the CFD simulation in the whole flow passage, the analysis of three-dimensional steady flow for the designed centrifugal turbine was carried out under both of design and off-design conditions, and the following results were obtained: the aerodynamic performance of centrifugal turbines with three kinds of volutes are almost the same under both of design and off-design conditions. Besides, the pear shaped volute shows slightly higher total efficiency, and its overall efficiency, stage internal efficiency and power are 87.36%, 85.79% and 484.88 kW, respectively.